Side effect profile and comparative tolerability of newer generation antidepressants in the acute treatment of major depressive disorder in children and adolescents: protocol for a systematic review and network meta-analysis : protocol - Türkmen, Cagdas; Sacu, Seda; Furukawa, Yuki; Cates, Angharad N. de; Schoevers, Robert A.; Kamphuis, Jeanine; Chevance, Astrid; Weisz, John R.; Emslie, Graham J.; Strawn, Jeffrey R.; Hetrick, Sarah E.; Efthimiou, Orestis; et al. (BMJ open, 2025)
Introduction Major depressive disorder (MDD) is among the most common psychiatric disorders in children and adolescents. While previous meta-analyses have synthesised evidence on the efficacy and acceptability of newer-generation antidepressants in this population, specific adverse events (AEs) remain poorly characterised. This is of high clinical importance, as AEs are burdensome for patients, can reduce treatment adherence and lead to discontinuation. Here, we present a protocol for a network meta-analysis designed to evaluate the specific AE profile and comparative tolerability of newer-generation antidepressants in children and adolescents with MDD. - Methods and analysis The planned study will include double-blind randomised controlled trials that compared one active drug with another and/or placebo for the acute treatment of MDD in children and adolescents. The following antidepressants will be considered: agomelatine, alaproclate, bupropion, citalopram, desvenlafaxine, duloxetine, edivoxetine, escitalopram, fluoxetine, fluvoxamine, levomilnacipran, milnacipran, mirtazapine, paroxetine, reboxetine, sertraline, venlafaxine, vilazodone and vortioxetine. The primary outcomes will include the number of patients experiencing at least one AE, specific non-serious AEs, serious AEs (eg, suicidal ideation) and AEs leading to treatment discontinuation. Published and unpublished studies will be retrieved through a systematic search in the following databases: PubMed, Embase, Cochrane Library (including the Cochrane Central Register of Controlled Trials), Web of Science Core Collection, PsycInfo and regulatory agencies’ registries. Study selection and data extraction will be performed independently by two reviewers. For each outcome, a network meta-analysis will be performed to synthesise all evidence. Consistency will be assessed through local and global methods, and the confidence in the evidence will be evaluated using the Confidence in Network Meta-Analysis web application. All analyses will be conducted in the R software. - Ethics and dissemination The planned review does not require ethical approval. The findings will be published in a peer-reviewed journal and may be presented at international conferences. - PROSPERO registration number CRD420251011399.
Gesehen am 18.12.2025